Design a low power modulator/demodulator for battery-less wireless sensor platform - Zhang, Yujing (2014)
Radio Frequency Identification (RFID) technology has various applications for automatically identifying and tracking purpose. RFID uses radio frequency signal for communication. Passive RFID tags uses input RF signal as power harvesting source as well. Wireless Identification and Sensing Platform (WISP) is a passive RFID with sensing and computing capability.